UTILIZATION OF BANANA FROND BRIQUETTE CHARCOAL AS AN ALTERNATIVE TO ENVIRONMENTALLY FRIENDLY TECHNOLOGY - Efriyani, Veni Efriyani; Wardana, Rendy Wikrama; Uliyandari, Mellyta; Johan, Henny; Saputra, Hendri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The purpose of this study is the use of banana frond briquette charcoal as an alternative to environmentally friendly technology. This type of research is an experiment. Experimental data collection techniques, documentation, and literature studies. The data analysis method in this study uses a quantitative approach. Banana frond briquettes are divided into 3 groups: A (81% banana frond charcoal: 19% adhesive), B (71% banana frond charcoal: 29% adhesive), and C (91% banana frond charcoal: 9% adhesive). The results of the banana frond briquette test on the C sample of 91% charcoal briquettes with 9% adhesive showed the best results with a calorific value of 4571 kcal/kg. The study concluded that the best calorific value in sample C with a charcoal composition of banana fronds was 91%; 9% adhesive was 4571 cal/kg.